Pembelajaran pada Masa Pandemi di Sekolah Dasar Daerah Perbatasan Republik Indonesia/Papua Nugini - Agus Kichi Hermansyah; Rudolfus Ruma Bay; Adi Sumarsono; Supriyadi Supriyadi (Faculty of Teacher Training and Education, Musamus University, 2022)
The pandemic's global impact has led to a variety of learning processes. One of the consequences is felt in the school learning process in the border areas of the Republic of Indonesia and Papua New Guinea. This study aims to describe the learning process in schools located in the Republic of Indonesia/Papua New Guinea border areas during the pandemic. This research is quantitative research with a survey approach. The research instrument used questionnaires and interviews, and the data processing used percentages. The results of this study indicate that the elementary school learning process in border areas implements the learning process through non-face-to-face learning in schools. The dominance of the learning method is task-based (55%), which is often used in communicating by telephone (56%). The domination of the wishes of teachers and parents is that the face-to-face learning process is carried out again and the desire of students to be able to meet friends at school again and the learning process does not burden parents. The learning process is still carried out by limiting students to come to school, but assignments are still given through communication media between teachers and students' parents, and student work is collected in schools represented by parents.